Molecular Bases of Corneal Endothelial Dystrophies - Schmedt, Thore (2011)
The phrase “corneal endothelial dystrophies” embraces a group of bilateral corneal conditions that are characterized by a non-inflammatory and progressive degradation of corneal endothelium. Corneal endothelial cells exhibit a high pump site density and, along with barrier function, are responsible for maintaining the cornea in its natural state of relative dehydration. Gradual loss of endothelial cells leads to an insufficient water outflow, resulting in corneal edema and loss of vision. Since the pathologic mechanisms remain largely unknown, the only current treatment option is surgical transplantation when vision is severely impaired. In the past decade, important steps have been taken to understand how endothelial degeneration progresses on the molecular level. Studies of affected multigenerational families and sporadic cases identified genes and chromosomal loci, and revealed either Mendelian or complex disorder inheritance patterns. Mutations have been detected in genes that carry important structural, metabolic, cytoprotective, and regulatory functions in corneal endothelium. In addition to genetic predisposition, environmental factors like oxidative stress were found to be involved in the pathogenesis of endotheliopathies. This review summarizes and crosslinks the recent progress on deciphering the molecular bases of corneal endothelial dystrophies.